2023
DOI: 10.1186/s13256-023-03981-3
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus presenting as lupus erythematosus tumidus and lupus nephritis: a case report

Abstract: Background Lupus nephritis and lupus erythematosus tumidus (LET) are uncommon manifestations of systemic lupus erythematosus (SLE), and their coexistence as the initial presentation of SLE is exceedingly rare. Here, we report such a case, emphasizing the diagnostic challenges and therapeutic implications of this unusual association. Case report A 38-year-old North African woman presented in Nephrology department with a history of lower extremity ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a series of 25 LET cases from Wake Forest University, four patients also had SLE, and one had DLE [ 1 ]. Hajji et al reported the case of a 38-year-old female who presented with biopsy-proven LET and class V lupus nephritis with positive antinuclear, SS-A, and dsDNA antibodies [ 18 ]. These cases lend support to the association of LET with other specific subtypes of CLE, as well as SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 25 LET cases from Wake Forest University, four patients also had SLE, and one had DLE [ 1 ]. Hajji et al reported the case of a 38-year-old female who presented with biopsy-proven LET and class V lupus nephritis with positive antinuclear, SS-A, and dsDNA antibodies [ 18 ]. These cases lend support to the association of LET with other specific subtypes of CLE, as well as SLE.…”
Section: Discussionmentioning
confidence: 99%